Expression of CD40 Ligand on T Cells and Soluble CD40 Ligand in Children With Kawasaki Disease: A Single-Center Preliminary Study From North India. Issue 5 (August 2021) - Jindal, Ankur Kumar; Rawat, Amit; Goel, Shubham; Shandilya, Jitendra; Saikia, Biman; Minz, Ranjana W.; Singh, Surjit
Abstract : Background/Objective: This study was done to examine the role of CD40 ligand (CD40L) in children with Kawasaki disease (KD). There is paucity of literature on this aspect of KD. Methods: This was a case-control study of patients with KD diagnosed at the Allergy Immunology Unit, Postgraduate Institute of Medical Education and Research, Chandigarh, India. CD40L expression on activated CD3+ T cells was measured using flow cytometry, and soluble CD40L (sCD40L) was measured using enzyme-linked immunosorbent assay. Results: We included 14 children with KD, 14 healthy controls, and 12 febrile controls for the purpose of this study. Mean percentage CD40L expression was higher in patients with KD (before administration of intravenous immunoglobulin [IVIg]) as compared with normal and febrile controls. This difference was statistically significant when compared with normal control ( p = 0.00; confidence interval [CI], 8.92–20.30), but was not statistically significant when compared with febrile controls ( p = 0.138; CI, −3.50 to 22.08). CD40L expression decreased after giving IVIg, but the difference was not statistically significant ( p = 0.073; CI, −1.04 to 19.73). Mean sCD40L values increased significantly after giving IVIg (when repeated after a median period of 11 days; p = 0.001; CI, −0.77 to −0.29). There was no statistically significant difference between mean sCD40L in patients with KD (before giving IVIg) as compared with normal and febrile controls ( p = 0.42; CI, −1.11 to −0.51 and p = 0.641; CI, −0.37 to 0.57, respectively). Conclusions: CD40L may have important role in the pathogenesis of KD. However, these results need to be validated in larger multicenter studies. Abstract : Supplemental digital content is available in the text.